Beban Kerja dan Work-Family Conflict terhadap Kinerja Pegawai yang Dimediasi Komitmen Organisasi - Trisafe Lukman Candra; Toni Herlambang; Budi Eko Satoto (BUDGETING : Journal of Business, Management and Accounting, 2022)
The purpose of this study was to determine directly or indirectly the effect of workload and WFC on employee performance through organizational commitment as an intervening variable at the village empowerment office of Bondowoso Regency. The number of samples in this study was 110 using the Nonprobability Sampling Technique. The analysis technique used is Structural Equation Model (SEM) using SmartPLS 3.2.8. The main finding of this study is to examine the coefficients of direct and indirect paths to improve employee work through the WFC workload variables, organizational commitment and employee performance. The results showed that workload had no significant effect on organizational commitment. Work-family conflict has a significant effect on organizational commitment. Workload, WFC, and organizational commitment have a significant impact on performance. Workload has no significant effect on employee performance when organizational commitment is an intervening variable. WFC positively affects employee performance through organizational commitment as an intervening variable. From the results of the study, it can be concluded that employees already have a clear division of duties so that there is no excessive workload and that employees have organizational commitment so that productivity and work performance increase. Keywords: Workload, Work Family Conflict, Employee Performance and Employee Commitment